1987
DOI: 10.1161/01.atv.7.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced accumulation and turnover of esterified cholesterol in injured rabbit aorta.

Abstract: Several hypotheses have been advanced as possible explanations for the effects of injury. One of these 8 is that removal of the endothelium eliminates a barrier to influx of macromolecules from plasma. Others 9 argue that the endothelium prevents efflux of macromolecules from the artery. At present, relatively few studies have considered the contribution of plasma cholesteryl ester influx to the observed excess cholesteryl ester accumulating in the artery This work was supported by Research Grant HL10933 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(30 reference statements)
2
9
0
Order By: Relevance
“…medial layer of the artery, these investigators observed a 30-60-fold increase in permeability to cholesteryl ester, primarily reflecting p-VLDL permeability immediately after injury. 13 If we assume that the HDL permeability of the artery as measured in the present study also reflects the permeability of the much larger /3-VLDL, then the permeability increase immediately after transplantation as observed in our study suggests that transplantation changes the surface of the artery in a manner similar to a more severe physical injury to the artery. The assumption about the proportionality between aortic permeability to HDL and aortic permeability to VLDL is based on findings in nontransplanted aortas of cholesterol-fed rabbits.…”
Section: Immune and Physical Damage To The Vesselsupporting
confidence: 56%
See 1 more Smart Citation
“…medial layer of the artery, these investigators observed a 30-60-fold increase in permeability to cholesteryl ester, primarily reflecting p-VLDL permeability immediately after injury. 13 If we assume that the HDL permeability of the artery as measured in the present study also reflects the permeability of the much larger /3-VLDL, then the permeability increase immediately after transplantation as observed in our study suggests that transplantation changes the surface of the artery in a manner similar to a more severe physical injury to the artery. The assumption about the proportionality between aortic permeability to HDL and aortic permeability to VLDL is based on findings in nontransplanted aortas of cholesterol-fed rabbits.…”
Section: Immune and Physical Damage To The Vesselsupporting
confidence: 56%
“…Such studies may have more general interest, as immune mechanisms may also be of importance for the development of the atherosclerotic plaque in nontransplanted arteries. 13 …”
Section: -mentioning
confidence: 99%
“…Two previous studies have estimated uncertainties in calculated values of intimal clearance and fractional loss that are induced by measurement uncertainties of the order likely in practice (24,26), using experimental conditions quite similar to the present study. Wootton et al (24) appplied random noise with zero mean and 1.5% SD to plasma radioacitvity data and random noise of zero mean and 5% SD to arterial wall radioactivity data, which produced uncertainties of 7% SD in calculated intimal clearance and 16% SD in cal-…”
Section: Methodsmentioning
confidence: 77%
“…Schwenke and Zilversmit (26) estimated that a 5% error in arterial wall radioactivity would produce an 8.5 to 14.5% error in calculated fractional loss and a 1.5 to 10% error in calculated intimal clearance (data calculated from Table 2 in reference 26).…”
Section: Methodsmentioning
confidence: 99%
“…27 It is possible that complex flow patterns behind the aortic valves in the aortic arch may also help explain the high permeability values in this aortic region. Experimental endothelial injury with a balloon catheter increased the influx of lipoproteins into the arterial wall, 29 and in the rat aorta, 37% of arterial foci with high permeability to Evans blue-labeled albumin were associated with endothelial cell death. 30 In the normal rabbit thoracic aorta, endothelial cell death is predominant in the lesion-prone sites.…”
Section: Regional Variation In Aortic Permeability To Ldlmentioning
confidence: 99%